2011
DOI: 10.1016/j.joca.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

History of knee injuries and knee osteoarthritis: a meta-analysis of observational studies

Abstract: History of knee injury is a major risk factor for the development of knee OA irrespective of study design and definition of knee injury. As one of the few modifiable/preventable risk factors, knee injury should be part of the future prevention programme in reducing the risk of knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(180 citation statements)
references
References 46 publications
5
170
2
3
Order By: Relevance
“…Some studies have used similar definitions to ours including non-weight bearing as a criteria for a significant knee injury; however, the duration of non-weight bearing seems variable across studies. Other studies have used outcomes such as duration of pain after the injury as a criterion for a significant injury [16]. Therefore, our definition may have affected our findings; nonetheless, we have demonstrated biologically plausible associations in both cohorts.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some studies have used similar definitions to ours including non-weight bearing as a criteria for a significant knee injury; however, the duration of non-weight bearing seems variable across studies. Other studies have used outcomes such as duration of pain after the injury as a criterion for a significant injury [16]. Therefore, our definition may have affected our findings; nonetheless, we have demonstrated biologically plausible associations in both cohorts.…”
Section: Discussionmentioning
confidence: 91%
“…Firstly, it is not clear whether the injury to the knee joint or the subsequent surgery leads to the development of secondary OA, as the available literature often refers to knee trauma without a clear distinction between the two [15,16]. Secondly, it is not known which structures comprising the knee joint, as determined by MRI, are affected by injury and hence contribute towards the progression of the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Persons who sustain a knee injury are 4.2 times more likely to develop OA than those without a history of knee injury. 9 Authors 3 of a retrospective medical record review suggested that PTOA accounts for approximately 10% of all cases of knee OA.…”
Section: Incidence and Prevalence Of Oamentioning
confidence: 99%
“…1 A systematic review found that patients with a previous history of traumatic knee injury are at increased risk of developing knee OA, regardless of specific injury. 2 It is vital for the maintenance of quality of life for individuals affected with OA that the treatment options available be able to reduce symptoms and restore quality of living. The painrelief benefits of traditional injection treatments are small to moderate and have a limited duration.…”
Section: Clinical Scenariomentioning
confidence: 99%